PENGARUH STRUKTUR MODAL, KEBIJAKAN UTANG, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Liana Nurul Afifah; Maretha Ika Prajawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
The purpose of this study is to determine the effect between capital structure, debt policy, and managerial ownership on firm value with profitability as a moderating variable. The sample in this study is Consumer Non Cyclical sector listed in the IDX for 2017-2021. Sample is taken using purposive sampling method consisting of 35 samples with 7 companies. Data were analyzed using multiple linear regression statistical tests and MRA using SPSS software version 25. The results showed that capital structure, debt policy, and managerial ownership has negative effect on firm value. Then profitability is able to moderate the relationship between managerial ownership and company value. While the capital structure and debt policy of the company's value is not able to be moderated by profitability.